India No. 1 (2016) Agreement between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of India for Co-operation in the Peaceful Uses of Nuclear Energy. London, 13 November 2015. ([2016-05-17]) - Unknown
No abstract available